1996
DOI: 10.1007/bf01441503
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of alternative refrigerants in the liquid phase

Abstract: Measurements of the thermal conductivity of five alternative refrigerants, namely, difluoromethane (HFC-32), pentafluoroethane ( H FC-125 ), 1,1,1-trifluoroethane (HFC-143a), and dichloropentafluoropropanes (HCFC-225ca and HCFC-225cb), are carried out in the liquid phase. The range of temperature is 253-324 K for HFC-32, 257-305 K for HFC-125, 268-314 K for HFC-134a, 267-325 K for HCFC-225ca, and 286-345 K for HCFC-225cb. The pressure range is from saturation to 30 MPa. The reproducibility of the data is bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 1 publication
1
30
1
2
Order By: Relevance
“…The dilute-gas thermal conductivity data of Haynes (Haynes, 1994) from NIST were used to obtain the dilute-gas coefficients in Table 6 (located in the Appendix), and the wide-ranging fluid measurements of both Haynes (Haynes, 1994) and of Le Neindre et al (Le Neindre, Garrabos, & Kim, 2001) were used to obtain the residual coefficients in Table 6. The value of qd -1 in Table 4 was obtained by fitting, while the other coefficients in Table 4 are from the generalized model of Perkins et al (R. A. Perkins et al, 2013) Measurements of other researchers (Lee, Kim, & Ro, 2001;Tanaka, Nakata, & Makita, 1991;Yata, Hori, Kobayashi, & Minamiyama, 1996) and the data used in regression (Haynes, 1994;Le Neindre et al, 2001) are shown in the deviation plots in Figures 107 and 108. As seen in the deviation plots, there are still discrepancies in the data, and future work would be useful to determine the most reliable data sets.…”
Section: R1123 (Trifluoroethylene)mentioning
confidence: 99%
“…The dilute-gas thermal conductivity data of Haynes (Haynes, 1994) from NIST were used to obtain the dilute-gas coefficients in Table 6 (located in the Appendix), and the wide-ranging fluid measurements of both Haynes (Haynes, 1994) and of Le Neindre et al (Le Neindre, Garrabos, & Kim, 2001) were used to obtain the residual coefficients in Table 6. The value of qd -1 in Table 4 was obtained by fitting, while the other coefficients in Table 4 are from the generalized model of Perkins et al (R. A. Perkins et al, 2013) Measurements of other researchers (Lee, Kim, & Ro, 2001;Tanaka, Nakata, & Makita, 1991;Yata, Hori, Kobayashi, & Minamiyama, 1996) and the data used in regression (Haynes, 1994;Le Neindre et al, 2001) are shown in the deviation plots in Figures 107 and 108. As seen in the deviation plots, there are still discrepancies in the data, and future work would be useful to determine the most reliable data sets.…”
Section: R1123 (Trifluoroethylene)mentioning
confidence: 99%
“…According to Yata et al [2], a linear relationship also holds for the thermal conductivity of refrigerants in the saturated liquid state, but Ro et al [3] correlated such data using a second-order polynomial:…”
Section: Pure-component Thermal Conductivitymentioning
confidence: 98%
“…For refrigerants, several investigators [2][3][4][5][6][7][8] represented the combined temperature and pressure dependence, of pure and specific binary and ternary refrigerant mixtures, by the following polynomial:…”
Section: Pure-component Thermal Conductivitymentioning
confidence: 99%
See 2 more Smart Citations